Nurse Actions In Preventing Nosocomial Infections In Post Surgical Wounds In RB2 A and RB2 B RSUP H. Adam Malik Medan - Fridella Grace Natalia Tarigan; Selvia Yolanda Dalimunthe (CV. AFDIFAL MAJU BERKAH, 2022)
Infection is the leading cause of death worldwide that can cause extreme pain and cause serious injury to cells or tissues. Nosocomial infections acquired or occurring in hospitals are related to the provision of health services in health care facilities and nurse actions are needed to prevent nosocomial infections by washing hands, using protective equipment, managing medical devices, disinfecting action sites, performing wound care and closure and waste management. . The design of this research is simple descriptive with the research sample being 44 nurses who work in RB 2A and 2B RSUP H. Adam Malik Medan. The sampling technique used is Total Sampling. The results of this study indicate that the characteristics of the respondents have worked for more than three years, namely 34 respondents (77.3%) with the education level of the most respondents being D3, namely 21 respondents (47.7%) and earning more than Rp. 1,500,000 there are 32 respondents (72.2%). The results showed that the actions of nurses in preventing nosocomial infections in post-surgical wounds were in the good category, namely 44 people (100%). For further research, it is recommended to conduct research on other factors that influence the occurrence of infection and the role of professional nurses in infection control as well as the nutritional needs of patients. 000 there are 32 respondents (72.2%). The results showed that the actions of nurses in preventing nosocomial infections in post-surgical wounds were in the good category, namely 44 people (100%). For further research, it is recommended to conduct research on other factors that influence the occurrence of infection and the role of professional nurses in infection control as well as the nutritional needs of patients. 000 there are 32 respondents (72.2%). The results showed that the actions of nurses in preventing nosocomial infections in post-surgical wounds were in the good category, namely 44 people (100%). For further research, it is recommended to conduct research on other factors that influence the occurrence of infection and the role of professional nurses in infection control as well as the nutritional needs of patients.